PENGARUH KEBIASAAN MEMBACA DAN DISIPLIN DIRI TERHADAP KEMAMPUAN MENULIS TEKS DESKRIPSI BAHASA INGGRIS - Heny Setiawati (Universitas Indraprasta PGRI, 2019)
This research is a kind of survey and aims to find out the effects of reading habit and self-discipline towards student’s descriptive text writing skill. The observed population of this research is students from state junior high schools in East Jakarta. The sample was gained through simple random sampling, which means that the researcher mixed the subjects in the population so that they will be considerably the same. The gained data was then analyzed by using correlation technique and multiple regressions. Previously, the prerequisite test before examining the regression test must be accomplished. The results of this research are: 1) There are significant effects of reading habit and self-discipline altogether towards descriptive text writing skill. It is proved by Sig.= 0.000 < 0.05 and Fobserved = 45.365; 2) There is a significant effect of reading habit towards student’s descriptive text writing skill. It is proved by Sig.= 0.000 < 0.05 and tobserved = 7.034; 3) There is a significant effect of self-discipline towards student’s descriptive text writing skill. It is proved by Sig.= 0.000 < 0.05 and tobserved = 3.788.